Bacterial surface appendages as targets for novel antibacterial therapeutics. (July 2014) - Steadman, David; Lo, Alvin; Waksman, Gabriel; Remaut, Han
The rise of multidrug resistant bacteria is a major worldwide health concern. There is currently an unmet need for the development of new and selective antibacterial drugs. Therapies that target and disarm the crucial virulence factors of pathogenic bacteria, while not actually killing the cells themselves, could prove to be vital for the treatment of numerous diseases. This article discusses the main surface architectures of pathogenic Gram-negative bacteria and the small molecules that have been discovered, which target their specific biogenesis pathways and/or actively block their virulence. The future perspective for the use of antivirulence compounds is also assessed.